Penggunaan Novel Sejarah sebagai Sumber Belajar Sejarah - Khusnul Khotimah (Jurnal Pendidikan Sejarah, 2018)
This study aims to find out how the use of historical novels as a source of learning in 15 State Senior High School of DKI Jakarta. The research method is descriptive method on survey technique, survey using Proportional Random Sampling technique.The results show that history teachers have a lot to know about the history novel. Nevertheless, the historical novel has not been widely used by history teachers. there are factors that have been used or not used the historical novel as a source of learning. The internal factors used by history novels by teachers are personally teachers depart from the hobby of reading fiction books especially historical novels and external factors the use of historical novels is that teachers feel the curriculum and school environment support the use of free and creative learning resources. Meanwhile, internal factor is not used by history novel by teacher is teacher do not know about the history novel external factor is, teacher feel student tend not interested to read. Both those who have used and have not used argue that the library in school is not sufficient enough for the availability of story books and novels about history. The benefits of using novel history according to the teacher is as one of the media development of literacy and can explain the imaginative nature and teachers are interested in using historical novels to support the affective side of students. Penelitian ini bertujuan untuk mengetahui bagaimana penggunaan novel sejarah sebagai sumber belajar di 15 SMA Negeri DKI Jakarta. Penelitian ini menggunakan metode deskriptif dengan teknik survey, surve menggunakan teknik Proportional Random Sampling. Hasil penelitian menunjukan bahwa guru sejarah sudah banyak mengetahui tentang novel sejarah. Meskipun begitu, novel sejarah belum cukup banyak digunakan oleh guru sejarah. Terdapat faktor atas sudah digunakan atau belum digunakannya novel sejarah sebagai sumber belajar. Faktor internal digunakannya novel sejarah oleh guru adalah secara pribadi guru berangkat dari hobi membaca buku fiksi terutama novel sejarah dan faktor eksternal digunakannya novel sejarah adalah guru merasa kurikulum dan lingkungan sekolah mendukung penggunaan sumber belajar yang bebas dan kreatif. Sementara, faktor internal tidak digunakannya novel sejarah oleh guru adalah guru tidak mengetahui tentang novel sejarah faktor eksternalnya adalah guru merasa anak didik cenderung tidak tertarik untuk membaca. Baik yang sudah menggunakan maupun belum menggunakan berpendapat bahwa perpustakaan di sekolah tidak cukup memadai untuk ketersediaan buku-buku cerita dan novel tentang sejarah. Adapun manfaat menggunakan novel sejarah adalah sebagai salah satu media pengembangan literasi dan dapat menjelaskan yang sifatnya imajinatif dan guru berminat menggunakan novel sejarah guna menunjang sisi afektif siswa.